In Vivo Studies Evaluating the Use of Contact Lenses for Drug Delivery. Issue 4 (April 2016) - Hui, Alex; Willcox, Mark
Abstract : ABSTRACT: This review highlights the current state of knowledge of in vivo testing of drug-delivering contact lenses. There has been a significant increase in interest in alternative means to deliver ocular pharmaceuticals, and within the past few decades, contact lenses have emerged as a vehicle of interest because of their biocompatibility and acceptance by both eye care professionals and the public. Using techniques such as molecular imprinting, vitamin E diffusion barriers, ionic reservoirs, and drug-impregnated films, significantly improved drug release kinetics have been observed in vitro . Extension of these results into in vivo studies has thus far been limited but has led to evidence of the viability of this drug delivery platform by demonstrating improved drug residence time, drug penetration, and clinical outcomes when compared with conventional therapy such as eye drops. The evidence supporting these improvements has occurred in both animal models and small human trials and is presented within this review.